The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsabm.9b00675
|View full text |Cite
|
Sign up to set email alerts
|

Poplar as Biofiber Reinforcement in Composites for Large-Scale 3D Printing

Abstract: The economic viability of the biofuel industry could be improved by adding a high-value revenue stream for biomass supply chains: bioderived composites for the rapidly expanding large-scale additive manufacturing industry (i.e., 3D printing). Using fibrillated fibers derived from biomass (e.g., Populus) to reinforce polymers for 3D printing applications would be less expensive compared to using conventional carbon fibers. Poplar fibers of different mesh sizes (<180, 180−425, 425−850, and 850−2360 μm) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…As both large-scale printers and use of wood and lignocellulosic-based fillers are more recent advancements to materials extrusion printing, there is little research done yet involving both. Currently, the only published research on large-scale printing with wood and lignocellulosic-based components comes from Zhao et al They used popular fibers, incorporated into a PLA matrix, to print architectural pieces and found that careful adjustment in printing processes, combined with use of selective fiber size, resulted in controlled viscosity and successful printing [ 103 ]. Despite the challenges of large-scale printing, researchers are finding new ways to overcome and excel at this novel methodology.…”
Section: Challenges and Opportunities In 3d Printing Of Wood Compomentioning
confidence: 99%
See 1 more Smart Citation
“…As both large-scale printers and use of wood and lignocellulosic-based fillers are more recent advancements to materials extrusion printing, there is little research done yet involving both. Currently, the only published research on large-scale printing with wood and lignocellulosic-based components comes from Zhao et al They used popular fibers, incorporated into a PLA matrix, to print architectural pieces and found that careful adjustment in printing processes, combined with use of selective fiber size, resulted in controlled viscosity and successful printing [ 103 ]. Despite the challenges of large-scale printing, researchers are finding new ways to overcome and excel at this novel methodology.…”
Section: Challenges and Opportunities In 3d Printing Of Wood Compomentioning
confidence: 99%
“…A common example of this is use of materials extrusion printing to produce building materials. Zhao et al printed prototype building materials using a poplar/PLA composite ( Figure 7 d) [ 103 ]. This material showed good printability and customization control.…”
Section: Applicationsmentioning
confidence: 99%
“…Chemical methods that improved molecular weight, orientation or the number of functional groups on monomers, increased the cross-linking density of biobased epoxy networks based on the dihydroeugenol product from CDL (106). Poplar fibers have also been directly incorporated into composites with polylactic acid (PLA) as a replacement for conventional carbon nanofibers that reinforce polymers for large-scale 3D printing applications (107).…”
Section: Utilizing Sugars and Aromatics For Highervalue Co-productsmentioning
confidence: 99%
“…Wood derivatives, such as wood flour and sawdust, as well as the components of wood, i.e., cellulose and lignin, are naturally abundant, biodegradable, biocompatible, and chemically modifiable materials that have shown promising potential for AM [ 5 , 6 ]. Existing research has shown that the practicability of incorporating wood-based materials in AM is largely dependent on the respective AM technique [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. At present, layer fabrication techniques using wood-based materials may be divided into two general categories: extrusion-deposition and granular bonding.…”
Section: Introductionmentioning
confidence: 99%
“…At present, layer fabrication techniques using wood-based materials may be divided into two general categories: extrusion-deposition and granular bonding. Extrusion-deposition fabrication primarily employs wood-plastic composite filaments that could be used in FDM [ 7 , 8 ]. In addition, studies have also shown that it is possible to extrude and deposit a slurry mixture of sawdust and adhesive directly to achieve similar AM results [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%